Pengembangan Sistem Informasi Website KPU Daerah Istimewa Yogyakarta - Argo Wibowo; Budi Susanto (Maranatha University Press, 2016)
Nowadays information is a very important data. Disclosure of information is necessary so the information that Â provided could be easily accessed by the public. We need a system where people can get access to information easily, and the system administrator can also process the data with valid information. The provided data must be quickly available to the public. Komisi Pemilihan Umum Daerah Istimewa Yogyakarta (KPU DIY) aware of the importance of the availability of information for the public. KPU DIY already have a website to provide information for public, but they still have access constraints in processing the information independently. So it is necessary to make a change of website management. This research aims to assist KPU DIY in building their website so it can be better used by the public and KPU DIY can independently manage their website content. Results of the questionnaire show that users are more interested, have more same viewpoint, as well as more motivated using the new website. The new website is also considered to be more efficient and new, thus users can use the system properly.Â Keywordsâ€” Content, Independent, Information, System.